PENGARUH KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERATING PADA GURU DI SMK NEGERI 4 KLATEN - Surono . (AKTUAL, 2014)
The purpose of this study is investigate influence of leadership and organization commitment to teacher perfomance with job satisfaction as moderating at The Government Vocational High School 4 at Klaten. The Hypothesis which have been formulated in this research is: there is influence of leadership and organization commitment to teacher perfomance with job satisfaction as moderating at The Government Vocational High School 4 at Klaten The research is a survey to the teacher of The Government Vocational High School 4 at Klaten. Data of this researh is primary. Data have been collected with quesionary was processed with, assumption of regression test, the moderated regression analysis, t test, F test and test of R2 The t test have been done in this research show that leadership and organization commitment have influence to teacher perfomance with job satisfaction as moderating at The Government Vocational High School 4 at Klaten as partial. The F test have been done show that the leadership and organization commitment have influence to teacher perfomance with job satisfaction as moderating at The Government Vocational High School 4 at Klaten as simultance. Keyword: leadership,organization commitment,perfomance, job satisfaction